Phosphoproteomic Analysis of Gossypol-Induced Apoptosis in Ovarian Cancer Cell Line, HOC1a - Lixu Jin (BioMed Research International, 2014)
Ovarian cancer is a major cause for death of gynecological cancer patients. The efficacy of traditional surgery and chemotherapy is rather compromised and platinum-resistant cancer recurs. Finding new therapeutic targets is urgently needed to increase the survival rate and to improve life quality of patients with ovarian cancer. In the present work, phosphoproteomic analysis was carried out on untreated and gossypol-treated ovarian cancer cell line, HOC1a. We identified approximately 9750 phosphopeptides from 3030 phosphoproteins, which are involved in diverse cellular processes including cytoskeletal organization, RNA and nucleotide binding, and cell cycle regulation. Upon gossypol treatment, changes in phosphorylation of twenty-nine proteins including YAP1 and AKAP12 were characterized. Western blotting and qPCR analysis were used to determine expression levels of proteins in YAP1-related Hippo pathway showing that gossypol induced upregulation of LATS1, which phosphorylates YAP1 at Ser 61. Furthermore, our data showed that gossypol targets the actin cytoskeletal organization through mediating phosphorylation states of actin-binding proteins. Taken together, our data provide valuable information to understand effects of gossypol on protein phosphorylation and apoptosis of ovarian cancer cells.